Clinical findings and prognostic factors for dogs undergoing elective versus non-elective cholecystectomies for gallbladder mucoceles - Kramer, Stacy Lynne (Kansas State University, 2020)
Objectives: The objectives of this multiinstitutional retrospective study were to compare and contrast post-operative morbidity between elective and non-elective cholecystectomy cases in dogs with gallbladder mucoceles, as well as to determine underlying risk factors and prognostic indicators of dogs with early gallbladder mucoceles and their need for surgical intervention. Animals: This study included 121 dogs with gallbladder mucoceles that had a cholecystectomy performed. Procedures: Medical records were reviewed for all dogs with a gallbladder mucocele between 2004-2018 that underwent a cholecystectomy. Dogs were classified into three categories: emergent (gallbladder rupture or systemic instability), urgent (systemic clinical signs, diabetic, or biliary duct distension), or elective (no clinical signs or bloodwork abnormalities). The method of common bile duct catheterization, for example, antegrade or retrograde catheterization, was noted if performed. Post-operative complications and survival were compared between groups. Results: Dogs that had a duodenotomy and retrograde common bile duct cannulation were 6.67 times more likely to develop a post-operative fever in comparison to dogs that had no common bile duct catheterization and 13.61 times more likely to develop post-operative fever in comparison to dogs that had normograde catheterization of the common bile duct. Dogs that had either urgent or emergent surgery were 3.45 and 4.3 times more likely, respectively, to die prior to discharge in comparison to those that had elective cholecystectomy. Conclusions and Clinical Relevance: Dogs undergoing elective cholecystectomies have a lower mortality rate than those undergoing urgent or emergent procedures. Duodenotomy with retrograde bile duct catheterization is associated with post-operative fever development.
Keywords: canine; gallbladder mucocele; cholecystectomy